2020
DOI: 10.1080/09669582.2020.1818764
|View full text |Cite
|
Sign up to set email alerts
|

Tourism, peace and sustainability in sanctions-ridden destinations

Abstract: Despite the widespread use of sanctions as a foreign policy tool in the absence of armed intervention and as a means to promote peace, there is notable absence of research on the effects of sanctions on the peacebuilding capacity of tourism and their relationship to the Sustainable Development Goals (SDGs). This situation is surprising given that both sanctions and tourism are promoted as a force for peace and reconciliation processes. Drawing upon international relations and political science and via semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…One strand of research suggests that the 2030 Agenda does not question the processes in which national and global wealth and power disparities are formed while also noting the limitations as to who is involved in the goal-setting process, how actors are linked and empowered, what resources they have and how and by whom transparency and accountability are ensured (Fukuda-Parr and McNeill, 2019;Kanie and Biermann, 2017). Some of the major governance challenges facing the SDGs implementation are collective action, trade-offs and accountability (Bowen et al, 2017); the role of democratic institutions and participation (Glass and Newig, 2019); inclusive goal-setting, detachment from the international legal and regulatory system and weak institutional arrangements at various scales (Biermann et al, 2017;Kanie and Biermann, 2017); health, food and gender equality (Dalby et al, 2019;Seyfi et al, 2022); interlinkages and synergies between goals and substantive content in a systemic perspective, policy coherence and policy integration (Weitz et al, 2018); and climate change and sustainable energy (Monkelbaan, 2019).…”
Section: Criticizing the Sustainable Development Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…One strand of research suggests that the 2030 Agenda does not question the processes in which national and global wealth and power disparities are formed while also noting the limitations as to who is involved in the goal-setting process, how actors are linked and empowered, what resources they have and how and by whom transparency and accountability are ensured (Fukuda-Parr and McNeill, 2019;Kanie and Biermann, 2017). Some of the major governance challenges facing the SDGs implementation are collective action, trade-offs and accountability (Bowen et al, 2017); the role of democratic institutions and participation (Glass and Newig, 2019); inclusive goal-setting, detachment from the international legal and regulatory system and weak institutional arrangements at various scales (Biermann et al, 2017;Kanie and Biermann, 2017); health, food and gender equality (Dalby et al, 2019;Seyfi et al, 2022); interlinkages and synergies between goals and substantive content in a systemic perspective, policy coherence and policy integration (Weitz et al, 2018); and climate change and sustainable energy (Monkelbaan, 2019).…”
Section: Criticizing the Sustainable Development Goalsmentioning
confidence: 99%
“…The ambiguous relationship between the SDG and the international human rights regime has also been criticized by feminist and human rights scholars (Esquivel, 2016; Winkler and Williams, 2017), and they contested the claim that the 2030 Agenda is universal, stating that it falls short of what is necessary to solve environmental and inequality issues (Vandemoortele, 2018; Seyfi et al , 2022). Others have suggested that the SDGs are rooted in a neoliberal politics of development that emphasizes economic growth as a tool to reduce inequality, resulting in unfair and exclusive policies rather than pursuing structural change (Bianchi, 2018; Bianchi and de Man, 2021; Hall, 2022).…”
Section: Criticizing the Sustainable Development Goalsmentioning
confidence: 99%
“…Post-Revolution Iran appears to be very apprehensive of non-Islamic cultural values and has peculiar foreign relations (Borjian, 2013;Davari & Aghagolzadeh, 2015;Iranmehr & Davari, 2017;Nameni, 2020Nameni, , 2022Perwaiz, 2007). Considering the restrictions imposed on Iran due to the sanctions the tourism industry in this country has suffered (Seyfi & Hall, 2019;Seyfi, Hall, & Vo-Thanh, 2020). Yet, currently, about 780 foreign students are studying at Tehran University of Medical Sciences (TUMS, International Students, 2021).…”
Section: Ethnocentrism and Iranian Medical Studentsmentioning
confidence: 99%
“…Mostafanezhad et al (2020, p. 2) also notes tourism as "a fundamental site through which geopolitical narratives are assembled". Nonetheless, given the pervasive application of sanctions as a blunt geopolitical instrument of statecraft in the post-Cold War era with their direct and indirect effects on tourism (Pratt & Alizadeh, 2018;Seyfi et al, 2020;Seyfi & Hall, 2019, 2020a, 2020b, 2020c, there is only limited research on sanctions in the current literature on tourism and geopolitics. This highlights the significance of developing a better understating of this frequently deployed tool of economic statecraft and geopolitics and the way in which tourism becomes a focus, or casualty of foreign policy decision-making (Hall, 2017b).…”
Section: Geopolitics Tourism and International Sanctionsmentioning
confidence: 99%
“…However, the COVID-19 crisis raises substantial questions about the legitimacy of international economic sanctions, which as well as affecting tourism-related mobility are an impediment to humanitarian crisis management and response measures (Knupp, 2020;Murphy et al, 2020;Seyfi et al, 2020;Takian et al, 2020). For example, in the context of the COVID-19 pandemic, the unilateral US sanctions regime on countries such as Cuba, Iran and Venezuela has been criticized for their hindrance of the capacity to respond to COVID-19 with calls for the Trump administration to temporarily lift sanctions against these countries for peaceful and humanitarian objectives and to help such countries' health systems combat the pandemic (Takian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%